Comparison of two insertion techniques of classic laryngeal mask airway: standard versus 90-degree rotation - Raghavan, P.; P., Mithun Raju; T., Arnold Plazid (International Journal of Research in Medical Sciences, 2017)
Background: Laryngeal mask airway (LMA) devices have been widely utilized as an alternative to tracheal intubation in various clinical situations. The rotation technique has been suggested to improve the insertion success rate of laryngeal masks. The objective of the present study was to compare the ease of insertion of laryngeal mask in terms of, success rate at the first attempt, number of LMA insertion attempts, time duration of LMA insertion and complications like blood stain on LMA and sore throat. Methods: This prospective cohort study was conducted to compare the success rate of insertion at the first attempts between standard technique and 90 degree rotational technique at Department of Anaesthesiology, Amala institute of medical sciences, Thrissur, India during the period from March 2014-september 2015. A total of 160 patients each group consisting of 80 was included in the study after meeting inclusion criteria. Success rate of insertion at first attempts, number of insertion attempts, and insertion time of successful attempt, overall success rate, blood staining of laryngeal mask airway (LMA) and postoperative sore throat were recorded. Results: Significant difference was existed between the two groups with regard to gender. Statistically insignificant differences were observed for demographics like age, weight, ASA grades between the two study groups. Significant differences were observed among the study groups on all findings of LMA insertion. Statistically insignificant difference was detected for the time of duration of LMA insertion and change in heart rate, but mean arterial pressure was found statistically significant between the two groups. Conclusions: This study found that 90 degree rotational technique has high success rate of insertion at first attempt & is less traumatic than standard technique.